Formulasi dan Uji Mutu Fisik Sediaan Sabun Cair Herbal Ekstrak Daun Kemangi (Ocimum sanctum L.): Formulation and Physical Quality Test of Basil Leaf Extract Herbal Liquid Soap (Ocimum sanctum L.) - Sukma Dewi Ayu Anggraini; Panji Ratih Suci; Cikra Ikhda Nur Hamida Safitri (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Acne is a skin problem that is often a problem for most teenagers in Indonesia. This acne can occur due to a lack of facial hygiene, which causes the growth of bacteria. Basil (Ocimum sanctum L.) is a plant that grows in Indonesia and contains alkaloids, saponins, flavonoids and tannins which can inhibit the growth of bacteria. The purpose of this study was to utilize Basil extract (Ocimum sanctum L.) into liquid soap preparation and evaluate the physical quality of the preparation. Basil extract (Ocimum sanctum L.) can be obtained by using the maceration method using 96% ethanol as a solvent. Liquid soap preparation formulations are made with extract concentrations of 2%, 4%, and 6% with a uniform liquid soap base. Evaluation of liquid soap preparations includes tests for homogeneity, organoleptic, pH, dispersibility, and high foam. The results of the three liquid soap formulations showed that the three formulations were homogeneous and there was no organoleptic change, the pH range of liquid soap 9-11 which fulfilled the pH requirements of liquid soap according to SNI No. 06-4085-1996, namely 8 - 11, the spreadability test range is 2.7 - 3cm and the foam height test range is 3 ? 8,5cm.